2021
DOI: 10.1097/ccm.0000000000004847
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Human Chorionic Gonadotropin Hormone-Derivative EA-230 in Cardiac Surgery Patients: A Randomized Double-Blind Placebo-Controlled Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Moreover, in several of these studies, CytoSorb therapy was applied as a single treatment of six hours per day (9, 10), and it is therefore plausible that the majority of cytokines were produced outside this therapeutic window. This might also explain why CytoSorb therapy applied during cardiopulmonary bypass did not affect plasma concentrations of IL-6 in 37 cardiac surgery patients (11), as cytokine concentrations are known to peak several hours after termination of CPB in these patients (11,20), and CytoSorb therapy in this particular study was ceased at the end of CPB (11). Given the pronounced effect on plasma cytokine concentrations in the present work, it appears plausible that these studies might have yielded different results if patient groups with a more pronounced cytokine response were selected and received more prolonged or continuous hemoadsorption treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in several of these studies, CytoSorb therapy was applied as a single treatment of six hours per day (9, 10), and it is therefore plausible that the majority of cytokines were produced outside this therapeutic window. This might also explain why CytoSorb therapy applied during cardiopulmonary bypass did not affect plasma concentrations of IL-6 in 37 cardiac surgery patients (11), as cytokine concentrations are known to peak several hours after termination of CPB in these patients (11,20), and CytoSorb therapy in this particular study was ceased at the end of CPB (11). Given the pronounced effect on plasma cytokine concentrations in the present work, it appears plausible that these studies might have yielded different results if patient groups with a more pronounced cytokine response were selected and received more prolonged or continuous hemoadsorption treatments.…”
Section: Discussionmentioning
confidence: 99%
“…First, timing and duration of CytoSorb therapy is of paramount importance (2). For instance, several previous studies have demonstrated that cytokine concentrations in cardiac surgery patients start to increase only several hours postoperatively (3, 4). Nonetheless, nine of ten studies in cardiac surgery patients in this meta-analysis applied CytoSorb therapy exclusively during cardiopulmonary bypass, when there are no circulating cytokines to clear.…”
Section: To the Editormentioning
confidence: 99%
“…EA-230 was also found to confer survival benefits in animals with abdominal sepsis [119]. Furthermore, EA-230 demonstrated excellent safety and tolerability in healthy volunteers participating in Phase I clinical trials [120]. IMX-942, a synthetic IDR peptide designed based on the sequence of IDR-1, first entered Phase I clinical trial in 2009 [116].…”
Section: Innate Defense Regulator (Idr) Peptidesmentioning
confidence: 99%